System for Effective Small Business Support - Pavlenko, Volodymyr; Lashko, Oksana (Lviv Politechnic Publishing House, 2021)
This paper considers the problem of developing specialized software designed to support small businesses. It substantiates the relevance of creating such systems; architecture has been offered; and the results of development have been given. For practical use, a specific subject area has been considered, which allows to clearly understand the purpose and outcome of the work. These materials can be used to obtain ready-made solutions during the development of a software package on this topic. This document can be considered as an introductory material for the various stages of the project to develop a system of effective support of small business.
Keywords: software development management; system modeling; business data processing; reconfigurable and self-configurable computer systems; data analysis; clientserver systems